The Effect of Economic Value Added (EVA), Market Value Added (MVA), Refined Economic Value Added (REVA) on Stock Prices and Returns Stock at Manufacturing Industries Who Listed on Indonesia Stock Exchange (BEI) - Nugroho, Mulyanto Nugroho (Archives of Business Research, 2018)
The development of returns stock of manufacturing companies shows a fluctuating movement from year to year. Movement of returns such as this indicates that the state of the manufacturing company is unstable so that it has an impact on returns the resulting stock. This uncertainty will certainly create a concern for investors who will invest shares in manufacturing companies. It is important for investors to analyze the condition of the company so that the investment can get benefit. One aspect of the company that can be assessed by investors is the company's performance through financial statements. Company performance measurement can be categorized into three groups, namely (1) Earning Measures, (2) Cash Flow Measures, and (3) Value Measure. The purpose of this study is to test EVA, MVA, and REVA on stock prices and returns stock. In this study using a sample of 104 manufacturing companies taken through random sampling in the 2014-2016 period. Data analysis and hypothesis testing in this study using Partial Least Square Path Modeling (PLS-SEM). The results show that EVA, MVA, and REVA have a significant positive relationship to stock prices and returns stock. By looking at the results of this study, it shows that performance appraisal uses EVA, MVA, and REVA methods have a strong influence on stock prices and returns stock. This shows that valuation based on value is important because each investment can’t escape the consequences of the emergence of capital costs as compensation for the funds used to finance the investment.